A Review Of Adoption Of E-Learning In Middle East Countries - Ahmad, Asmala; Nemeah, Ali Fahem; Mohammed, Hassan (Caomei Publishers, 2018)

(untitled)
E-learning has provided men with new opportunities in teaching-learning procedures.A historical review of educational systems literature reveals that e-learning has spread out among people much faster than any other learning methods.E-learning,as a state-of-the-art technology,has caused great innovations in materials development in those societies in which new methods and procedures could hardly ever been accepted.Technological innovations and the development of telecommunications such as Television Stations and Channels,Satellites, Mobile,and Internet have made it possible for the children and teenagers in the Middle East to access to the latest news and information.Of course,these developments have endangered both political and educational systems in some aspects.The present paper while pointing to some of the recent developments in the field of elearning in the Middle East,tries to examine the political and educational systems reactions to this phenomenon.